Genome-wide association study identifies two risk loci for tuberculosis in Han Chinese. Issue 1 (December 2018) - Zheng, Ruijuan; Li, Zhiqiang; He, Fusheng; Liu, Haipeng; Chen, Jianhua; Chen, Jiayu; Xie, Xuefeng; Zhou, Juan; Chen, Hao; Wu, Xiangyang; Wu, Juehui; Chen, Boyu; et al.
Abstract Tuberculosis (TB) is an infectious disease caused byMycobacterium tuberculosis (Mtb ), and remains a leading public health problem. Previous studies have identified host genetic factors that contribute toMtb infection outcomes. However, much of the heritability in TB remains unaccounted for and additional susceptibility loci most likely exist. We perform a multistage genome-wide association study on 2949 pulmonary TB patients and 5090 healthy controls (833 cases and 1220 controls were genome-wide genotyped) from Han Chinese population. We discover two risk loci: 14q24.3 (rs12437118, P combined = 1.72 × 10−11, OR = 1.277, ESRRB ) and 20p13 (rs6114027, P combined = 2.37 × 10−11, OR = 1.339, TGM6 ). Moreover, we determine that the rs6114027 risk allele is related to decreasedTGM6 transcripts in PBMCs from pulmonary TB patients and severer pulmonary TB disease. Furthermore, we find thattgm6 -deficient mice are more susceptible toMtb infection. Our results provide new insights into the genetic etiology of TB. Genetic risk loci for tuberculosis (TB) have so far been identified in African and Russian populations. Here, the authors perform a three-stage GWAS for TB in Han Chinese populations and find two risk loci nearESRRB andTGM6 and further demonstrate thattgm6 protects mice fromMtb infection.